Introduction to the Special Section on Social Computing and Social Internet of Things - Hsu, Ching-Hsien; Montenegro Marin, Carlos Enrique; González-Crespo, Rubén; Mohamed El-Sayed, Hassan Fouad (IEEE Transactions on Network Science and Engineering, 2023)
The papers in this special section focus on social computing and the social Internet of Things (SIoT). SIoT is a new and latest paradigm that extends Internet of Things. This provides an ideal platform for interconnected devices and objects to effectively interact across social platforms for the betterment of the community on a whole. Any Social Internet of things based system means that the data is distributed in nature and focuses on the interest of a larger group of people than a particular individual. Thus social Internet of things have a wide scope and can be used to develop a wide range of applications that involves a group of people or community working towards accomplishing a common objective such as joint ventures, office setup, co-ownerships and so on. Social Computing may be defined as the study of the collaborative behavior of a group of computer users working on some common objectives.
Keywords: collaborative behavior; computer users; joint ventures; large groups; social computing; special sections; Scopus; JCR